Perancangan Sistem Informasi Peramalan Penjualan Meubel Menggunakan Metode Moving Average (Studi Kasus Toko Meubel Sumber Rejeki) - Syahrul Mubarak Abdullah; Widya Novianti (Informasi Interaktif, 2022)
Sumber rejeki furniture is a shop that is engaged in the sale of furniture items such as chairs, tables, beds, cabinets, and clocks. Currently, the source of fortune furniture store does not have a supporting application so that data collection is still manual. This research was conducted to build an information system application for furniture sales forecasting using Moving Average method which is computerized which is more effective than the manual system. The benefit of this forecasting method is to estimate or predict the inventory of goods that will be provided by the fortune source furniture store in the following month. This web application is made using PHP because it can be connected to a MySQL database and all the tools we need in building application programs for Windows quickly and efficiently